Unformatted text preview: A in the last equation gives det(adj A ) = (det A ) 2 . (ii) . Also from equation (1) µ 1 det A A ¶ adj A = I 3 , so adj A is non–singular and (adj A )1 = 1 det A A. ±inally A1 adj( A1 ) = (det A1 ) I 3 and multiplying both sides of the last equation by A gives adj( A1 ) = A (det A1 ) I 3 = 1 det A A. 48...
View
Full
Document
This note was uploaded on 12/19/2011 for the course MAS 3105 taught by Professor Dreibelbis during the Fall '10 term at UNF.
 Fall '10
 Dreibelbis

Click to edit the document details